Problematic Use of the Internet in Subjects With Bipolar Disorder: Relationship With Posttraumatic Stress Symptoms - Carmassi, Claudia; Bertelloni, Carlo Antonio; Cordone, Annalisa; Dell'Oste, Valerio; Pedrinelli, Virginia; Barberi, Filippo Maria; Massimetti, Enrico; Bui, Eric; Dell'Osso, Lliliana (Frontiers in Psychiatry, 2021)
Background: Literature show a high risk for Problematic Use of the Internet (PUI) in mood disorders, especially in Bipolar Disorder (BD). In subjects with BD, traumatic events and Post-Traumatic Stress Disorder (PTSD) are related to alcohol or substance use disorder, as well as to gambling disorder. However, little is known about the possible association between traumatic exposure and PUI. The present study was aimed at examining the relationship between PUI and trauma exposure, besides PTSD symptoms, in subjects with BD. Methods: a sample of 113 subjects with BD was screened to putative PUI. Furthermore, they completed the Trauma and Loss Spectrum Self-Report (TALS-SR) to assess traumatic events and post-traumatic stress symptoms. Results: Twenty-four subjects (21.2%) reported Putative PUI. Subjects with putative PUI presented significantly higher scores in the TALS-SR domains Potentially Traumatic Events, Re-experiencing, Maladaptive coping and Arousal, as well as in the TALS-SR total score. In a logistic regression model, a positive association emerged between Potentially Traumatic Events and Arousal TALS-SR domains and putative PUI. Conclusion: One in five patients with BD screened positive for PUI. A significant association between PUI and lifetime traumatic events as well as PTSD symptoms emerged, highlighting the relevance of the comorbidity between PTSD and PUI in subjects with BD.